Cloning and expression of cDNA for salmon growth hormone in Escherichia coli - Sekine, Susumu (1985)
cDNA clones encoding chum salmon (Oncorhynchus keta) growth hormone (sGH) have been isolated from a cDNA library prepared from chum salmon pituitary gland poly(A)(+) RNA. Synthetic oligodeoxynucleotide mixtures based on amino acid residues 23-28 of sGH were used as hybridization probes to select recombinant plasmids carrying the sGH coding sequence. The complete nucleotide sequence of sGH cDNA has been determined. The cDNA sequence codes for a polypeptide of 210 amino acids, including a putative signal sequence of 22 amino acids. The 5′ and 3′ untranslated regions of the message were 64 and 426 bases long, respectively. Mature sGH was efficiently expressed in Escherichia coli carrying a plasmid in which the sGH cDNA was under control of the E. coli trp promoter; sGH comprised about 15% of the total cellular protein in such bacteria. The partially purified sGH from E. coli stimulated the growth of rainbow trout and the activity was indistinguishable from that of natural sGH.